Pulsed radio frequency characterisation on 28 nm complementary metal–oxide semiconductor technology. Issue 1 (1st January 2015) - Sahoo, A.K.; Fregonese, S.; Scheer, P.; Celi, D.; Juge, A.; Zimmer, T.
Abstract : The influence of electrothermal behaviour on radio frequency (RF) performances of 28 nm bulk complementary metal–oxide semiconductor technology is examined. Biased continuous‐wave RF and pulsed RF (applying different DC pulse and RF pulse width combinations) characterisations are performed within the 1–30 GHz frequency domain at room temperature and the transit frequency ( f T ) is extracted at 15 GHz frequency. It has been found that the degradation in f T on I/O devices is about 3 GHz because of the self‐heating effect.